2010
DOI: 10.2340/00015555-0975
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Human Leukocyte Antigen Complex on the Development of Cutaneous Fibrosis: An Immunogenetic Perspective

Abstract: A number of aesthetically and physically distressing disorders of the skin come under the general term "cutaneous fibrosis", all sharing a common abnormal wound healing process. These disorders are often incurable and effective treatments remain to be established and, as such, they present a significant burden for patients and a therapeutic challenge for clinicians. The aim of this review is to investigate the evidence of either positive or negative associations of the human leukocyte antigen (HLA) system with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 97 publications
0
6
0
Order By: Relevance
“…Different theories exist to explain the etiology of keloids, including elevated skin tension (9, 10), hypoxia (11), chronic inflammation (12), autoimmune (1315), genetics (16, 17), and vascular factors (18), none of which, however, are independently sufficient to do so. To date, options for keloid treatment are poorly defined, in part due to unsatisfactory outcomes of current treatments and the poor quality of evidence surrounding their use.…”
Section: Introductionmentioning
confidence: 99%
“…Different theories exist to explain the etiology of keloids, including elevated skin tension (9, 10), hypoxia (11), chronic inflammation (12), autoimmune (1315), genetics (16, 17), and vascular factors (18), none of which, however, are independently sufficient to do so. To date, options for keloid treatment are poorly defined, in part due to unsatisfactory outcomes of current treatments and the poor quality of evidence surrounding their use.…”
Section: Introductionmentioning
confidence: 99%
“…C5orf13 (NREP) expression is linked to hypertrophic scar [17]. This points out that hypertrophic scar and the function associated with NREP can only be performed once the cell is marked by HLA genes [18]. Even though the relationship of these genes with hypertrophic scar was already known [17, 18], there was no knowledge about how it was regulated.…”
Section: Resultsmentioning
confidence: 99%
“…There is a clear association between specific HLA alleles and cutaneous fibrosis. Specific examples of cutaneous fibrosis include hypertrophic scars (HS) among others [18]. …”
Section: Resultsmentioning
confidence: 99%
“…Human leucocyte Antigen (HLA), key genes responsible for the development of the cellular immune system, have been shown to play a critical role in not only autoimmune conditions but also in benign and malignant conditions.Mutations on some of the alleles are thought to be responsible for the development of a number of autoimmunedisorders such as celiac disease, anky losing, spodylisthesis and rheumatoid arthritis [11][12]. Even closer to keloids Sclerotic skin conditions such as sarcoidosis and systemic sclerosis have also been shown to have associations with particular alleles [13].Though keloids disease are not classi ed as autoimmune disease several studies have shown an association between some alleles and the disease bringing to the fore possibilities that the immune system could play a critical role in keloid formation.Wen-Sheng Lu found DQB1*0501, B*07-DRB1*15, DQB1*0503-DRB1*15 (P<0.05) to be associated with keloid formation among Chinese Ham patients cohorts [14]. Another study by Brownet alfound an association between HLA DRB1*15 and keloid formation in apatient cohort of Caucasians [15].…”
Section: Discussionmentioning
confidence: 99%